Soccer legends. Women's 2026 : stats, profiles, top players - Pettman, Kevin (Welbeck Children's Books, 2025)
"Showcasing the top 100 women soccer players in the modern game, Women's Soccer Legends 2025 offers the latest facts and stats of players in every position who play in the elite leagues. With a star profile on each page, this visually arresting stats book is packed with incisive data and includes stunning heat maps that show the pitch movements of each player."--Publisher.